ANALISIS KEBIJAKAN PENDIDIKAN INKLUSI - Muhammad Amir (Jurnal Tomalebbi, 2022)
Abstract: Inclusive education is regular education that is tailored to the needs of students who have disabilities and/or have the potential for intelligence and special talents in regular schools in a systemic unit. Inclusive education accommodates all children with special needs who have a normal IQ, intended for those who have disabilities, special talents, special intelligence and or who require special service education. The foundation of inclusive education is the Law on the National Education System chapter IV article V concerning the rights and obligations of citizens. The purpose of inclusive education is to provide the widest opportunity for all students who have physical, emotional, mental and social disabilities or have the potential for intelligence or special talents to obtain quality education according to their needs and abilities.